A Comparative Legal Analysis Of The Legislation Of Uzbekistan And Switzerland In The Field Of Contract Formation, Amendment, And Termination - Umirzokov, Shohrukh; Kholikulov, Elyorjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article provides a comparative legal analysis of the provisions of the Civil Code of the Republic of Uzbekistan and Swiss contract law governing the formation, amendment, and termination of contracts. The study examines in detail the concept of a contract, the principle of freedom of contract, types of contracts, the fundamental rules of contract formation, the form of contracts, mandatory contract formation, as well as the procedures for amending and terminating contracts. Through comparative analysis, the distinctive features, advantages, and potential areas for further development of national legislation are identified.